Development, participation and community psychology - Rozas, Germán (Revista de Psicología, 1992)
The urban-industrial style has demonstrated its quality as a concentrator of wealth, exclusive, generating great social inequalities. Furthermore, as the structural historical approach raises, problems such as: dualism, extraversion, disarticulation, imbalance, instability, dependency; They are serious consequences that leave deep scars in our Latin American societies (Bouviers, 1989). On the other hand, from the psychological and cultural point of view, the abuse of traditions, ancestral schemes of knowing work, religious-political mechanisms of social control, integrated mental health systems with the political and social, etc., produce and have produced a destruction of our communities, especially the most autochthonous ones, if one can speak of such communities (Rozas, 1989),